'All these things one has to endure from these Germans': German Stage Characters as Means to Criticize Changing Social Positions in Seventeenth-century Amsterdam. (2nd January 2018) - Ferket, Johanna
Abstract : In seventeenth-century Dutch theatre many stereotypical German characters appeared on the stage. Uncouth, ridiculous Germans speaking Dutch/German pidgin became a stereotypical joke in comic theatre, and this caricature enhanced the reception and entertainment value of a play. Moreover, playwrights also criticized or denounced 'moffen' ('Krauts') in Amsterdam as welfare-grabbers or social-climbers. Criticizing Germans was relatively safe for a playwright. Laughing at 'others' created a sense of solidarity among the audience, 'us' vs. 'them'. Criticizing Dutch culture and populace, however, involved a risk for the author and actors. The audience could take the criticism personally and since theatre needed an audience to survive, this could be very harmful. An author therefore had to anticipate the response of the audience. Because of their relative proximity to the Dutch people, some authors inserted German characters into their plays as instruments to criticize the foibles in Dutch society and class relations in particular. They criticized the exuberance of Amsterdam's society, the hypocrisy of rich upstarts, the naivety of those who are easily convinced by fancy titles and members of the working class such as handmaidens with ambition to climb the social ladder.